Unusual branching pattern of brachial artery with abnormal superficial palmar arch. - Srinivasa Rao Bolla,; Sashi Kumar J,; Saikat Roy,; Narendra Pamidi,; Raghu Jetti, (Department of Surgery, UKM Medical Centre, 2012)
Brachial artery is the chief artery of upper limb. Superficial palmar arch plays an important role in most of the traumatic events and the surgical procedures of the hand. The arterial variations of upper limb are useful for vascular surgeons, interventional radiologists, plastic surgeons. The authors report a case of high origin of superficial ulnar artery with abnormal formation of superficial palmar arch.